Arterio-Venous Differences in the Components of the Fibrinolytic Enzyme System - Ogston, D; Ogston, C. M; Bennett, N. B (Thrombosis and Haemostasis, 1966)
1. The concentration of the major components of the fibrinolytic enzyme system was compared in venous and arterial blood samples from male subjects.2. The plasminogen activator concentration was higher in venous blood and the arterio-venous difference increased as its concentration rose, but the ratio of the arterial to venous level remained constant.3. No arterio-venous difference was found for anti-urokinase activity, antiplasmin, plasminogen and fibrinogen.4. It is concluded that venous blood determinations of the components of the fibrinolytic enzyme system reflect satisfactorily arterial blood levels.